PENGARUH PRICE FAIRNESS TERHADAP KEPUTUSAN MENGINAP TAMU BILIQUE HOTEL BANDUNG - Irbadi, Wakhdan (2014)
Salah satukota di Indonesia yang memilikipotensi beragam dari sisi produk wisata, sejarah, budaya sertakeindahan anugerah alam ialahBandung. SebagaiIbu Kota PropinsiJawa Barat, Bandung dikenalmenjadikotatujuanwisata yang banyakdiminatibaikolehwisatawannusantaramaupunmancanegara.Semakinberkembangnyakepariwisataan di Kota Bandungakansemakinmemerlukanfasilitassertasaranapenunjangsemisal hotel yang harusselaluditingkatkankualitasdankuantitasnya.Dukungan dari pemerintahkota serta semakin tingginya permintaan pasar akan pemenuhan kebutuhan penginapan, menjadikanjumlah hotel di Kota Bandungtumbuhbegitupesat, hinggamenciptakantingginyatingkatpersaingankhususnyasesama hotel bintangtiga di Kota Bandung dalammemperebutkankeputusanmenginaptamu. Hal serupajugadialamiBilique Hotel, selamaduatahunterakhir, huniankamardanjumlahtamufree individual traveler yang menginapmengalamipenurunan. Salah satuupaya yang dilakukanBilique Hotel untukmeningkatkanhuniankamarnyaadalahdenganmenerapkanstrategipenetapanhargamelaluiprice fairness.Variabelbebas (X) dalampenelitianiniadalahprice fairnessyang terdiridaridistributive fairness, consistency,pricing honesty, the right of influence and co-determinationdanfair dealing, sedangkan untuk variabel terikat (Y) adalah keputusan menginap tamu yang meliputispesifikasiproduk, salurandistribusi,jumlahpembelian, waktupembeliandanmetodepembayaran. Jenispenelitian yang digunakanadalahdeskriptifdanverifikatif, sedangkanteknikpenarikansampelnyamenggunakandisproportionate stratified random sampling. Objekpenelitianiniadalahtamufree individual traveler yang menginap di Bilique Hotel, sedangkanteknikpengumpulan data dilakukanmelaluiwawancara, kuesionersertastudikepustakaan. Mengenaiteknikanalisis data yang digunakanadalahregresi linear bergandadenganmenggunakansoftware computer SPSS 20 for Windows.Hasilpenelitiandiketahuibahwa sub variabel yang memilikipengaruhsignifikanterhadapkeputusanmenginaptamufree individual traveler di Bilique Hotel adalahdistributive fairness, pricing honestydanfair dealing. Penelitianinijugamenyediakanrekomendasipotensialuntukpihakmanajemen hotel dalamusahameningkatkanhuniankamar. One of cities in Indonesia which has potential range of tourism product, history, culture and natural beauty is Bandung. Asthe capitalof WestJava, Bandungwas known to beone of themost preferreddestinationsbothdomestic and foreigntourists. The growth of tourism in the Bandung City will increasingly require facilities such as hotels that should be improved quality and quantity. Support from city government as well as the increasing market demand for the fulfillment of needs in accommodation, bringing the number of hotels in Bandung is growing rapidly and create a high level of competition especially for three-star hotels in getting guest's decision to stay. A similar thing happened in Bilique Hotel, during the last two years, room occupancy and a number of free individual traveler guest who stays has decreased. One of the efforts made to improve the Bilique Hotel room occupancy is to implement pricing strategies through price fairness. The independent variable (X) in this study is price fairness that composed from distributive fairness, consistency, pricing honesty, the right of influence and co-determination and fair dealing, while the dependent variable (Y) is a decision to stay which includes product specifications, distribution channels, amount of purchase, time of purchase and method of payment. This type of research is descriptive and verification, whereas the sample withdrawal techniques using disproportionate stratified random sampling. The object of research is a free individual traveler guests who stays in Bilique Hotel, while the techniques of data collection through interviews, questionnaires and literature studies.Data analysis techniqueused in this study ismultiple linear regressionusing thecomputer softwareSPSS20for Windows. Results reveal that the sub-variables that have a significant effect on the decision of a free individual traveler guest stay in Bilique Hotel is distributive fairness, pricing honesty and fair dealing. This study also provides potential recommendations for hotel management to increase occupancy.